The determination of joint roughness coefficient using three-dimensional models for slope stability analysis - Kim, D.H.; Gratchev, I.; Poropat, G.V. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Joint roughness coefficient (JRC) is one of the important parameters to determine shear strength of joints. JRC values are generally measured using profile gauges and estimated by comparing the surface profiles with typical roughness profiles. Therefore, the values can be subjective and vary depending on personal experience of an engineer. Digital photogrammetry methods provide 3D models based on high resolution digital images, and thus JRC values can be more objectively estimated from photogrammetry analysis using linear profile data. This paper seeks to investigate the feasibility of using the photogrammetry method to obtain JRC values. Photogrammetry surveys were performed at several slope sites, and JRC values were estimated using 3D images. To investigate the effect of resolution of digital images, the JRC values were first obtained using different distances between the slope and camera, and then compared with the roughness profiles which were manually measured by means of a Barton’s comb. A computer analysis using the distinct element code UDEC was also performed to better understand the effect of JRC on the stability of slopes.